2002
DOI: 10.1002/ijc.10584
|View full text |Cite
|
Sign up to set email alerts
|

Target validation for genomics using peptide‐specific phage antibodies: A study of five gene products overexpressed in colorectal cancer

Abstract: Genomic approaches are providing a wealth of information on differential gene expression in cancer. To identify the most interesting genes amongst the many identified, highthroughput methods for analysis of genes at the translational level are required. We have used a rapid method for the in vitro selection of antibodies to peptide antigens for the generation of probes to 5 gene products that we have found to be overexpressed in colorectal cancer. The rationale of our study was to select a non-immune phage dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
84
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 32 publications
20
84
0
2
Order By: Relevance
“…Therefore, more in vivo studies are needed for comprehensive understanding of roles of SIRT1 in cancer. Our finding that SIRT1 is an important downstream effector of NAMPT for oxidative stress in prostate cancer cells is in agreement with the previous finding in normal human vascular smooth muscle cells (van der Veer et al, 2007). However, our study does not exclude the contribution of other sirtuins.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, more in vivo studies are needed for comprehensive understanding of roles of SIRT1 in cancer. Our finding that SIRT1 is an important downstream effector of NAMPT for oxidative stress in prostate cancer cells is in agreement with the previous finding in normal human vascular smooth muscle cells (van der Veer et al, 2007). However, our study does not exclude the contribution of other sirtuins.…”
Section: Discussionsupporting
confidence: 91%
“…Increased expression of NAMPT was previously reported in colorectal cancer (Hufton et al, 1999;Van Beijnum et al, 2002). A specific small molecule inhibitor of NAMPT, FK866, inhibits cancer cell growth and induces apoptosis by NAD þ depletion (Hasmann and Schemainda, 2003).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…PBEF1 (PBEF1/Nampt/Visfatin) has been reported to be overexpressed in primary CRC [22,29]. Later, in agreement with our results, Nakajima et al found that visfatin levels in patients with CRC were significantly higher than those of the controls [9].…”
Section: Discussionsupporting
confidence: 42%